Learning to Collaborate through Collaborative Professional Learning: An Exploration of Social Learning Experiences - Tarwiyah, Siti; Dewi, Nuna Mustikawati; Sukarni, Semi (UNIB Press, 2024)
Collaboration becomes a supporting component of professional learning. Teachers’ experiences become the determining factor of the attainment a professional learning program. This study is aimed at exploring the experiences of teachers of two schools with different qualification by answering the following questions: (1) How are the programs of collaborative professional learning enacted to enhance the teachers’ teaching strategy and digital literacy?, (2) How do the teachers’ experiences in their collaborative professional learning impact on their policy of professional learning? This study is a qualitative case study. In order to answer its questions, this study involved 8 language teachers –Arabic, English, Indonesian, and Javanese language- from 2 schools. Teachers from a reputable school were paired up with those from an undistinguished school to engage in a collaborative professional learning program focusing on teaching strategy and digital literacy. Data analysis involved content analysis convention of Krippendorff (2013). The program is a need-based program, which is put in different social context and built to make each participant familiar, collaborate to learn, to practice, and to implement. Putting the program into different social context facilitates participants to learn through attention, retention, reproduction, which then influences their policy of professional learning.